Doubling fusion power with volumetric optimization in magnetic confinement fusion devices - J. F. Parisi; J. W. Berkery; A. Sladkomedova; S. Guizzo; M. R. Hardman; J. R. Ball; A. O. Nelson; S. M. Kaye; M. Anastopoulos-Tzanis; S. A. M. McNamara; J. Dominski; S. Janhunen; et al. (Physical Review Research)
A technique, volumetric power optimization, is presented for enhancing the power output of magnetic confinement fusion devices. Applied to a tokamak, this approach involves shifting the burning plasma region to a larger plasma volume while introducing minimal perturbations to the plasma boundary shape. This edge perturbation—squareness—is analogous to pinching and stretching the edge boundary. Stability calculations confirm that this edge alteration is compatible with maintaining plasma stability. This optimization method for optimizing fusion power output could improve the performance of magnetic confinement fusion power plants.